Pengaruh Sikap Dalam Pengembangan Organisasi (Kajian Teoris) - Atbar, Samuel (PAPSEL Research and Consulting, 2025)
Public organizational development is a crucial aspect in realizing effective and efficient service delivery. Employees’ attitudes toward organizational change play a key role in determining the success of this process. This article employs a literature review method to analyze the influence of attitudes in public organizational development. The review findings indicate that positive attitudes, such as openness to change and work commitment, significantly support bureaucratic reform. A competency- and performance-based approach serves as the foundation for building an adaptive work culture. Recommendations include strengthening attitude development programs, effective communication, and inspiring leadership to support organizational change in the public sector. Keywords: attitude, public organizational development, bureaucratic reform, competency, performance